Editing Talk:1047: Approximations
Revision as of 02:34, 20 May 2014 by 108.162.215.89 (talk) (added: Dgbrt, yes, sin(6π/7)=sin(π/7). Simple proof: sin(6π/7)=sin(π-π/7)=sin(π)cos(-π/7)+cos(π)sin(-π/7)=0*cos(-π/7)+(-1)*(-sin(π/7))=0+sin(π/7)=sin(π/7))
Please sign your posts with ~~~~ |
Warning: You are editing an out-of-date revision of this page. If you save it, any changes made since this revision will be lost.
Warning: You are not logged in. Your IP address will be publicly visible if you make any edits. If you log in or create an account, your edits will be attributed to your username, along with other benefits.